Dinamika Perkembangan Remaja Akhir dan Implikasinya dalam Dunia Pendidikan Islam - Lestari, Septia Sri; Suryana, Ermis; Zulhijra, Zulhijra (Lembaga Penelitian dan Pengabdian kepada Masyarakat, UIN Sultan Aji Muhammad Idris Samarinda, 2025)
Islamic education, as a system that integrates scientific and religious aspects, plays a strategic role in nurturing the younger generation. This study aims to understand the dynamics of late adolescent development and to identify its implications for Islamic education approaches in the school environment. The research was conducted at SMK NU Buay Madang using a qualitative approach through observation, in-depth interviews, and documentation. The findings indicate that late adolescents face identity crises, the influence of social media, and complex moral dilemmas. Islamic education is therefore required to develop dialogical, contextual, and spiritual approaches to effectively support the process of personality and religious formation in students. This study recommends the importance of mentoring programs, moral reinforcement, and religious activities that are relevant to the realities of adolescents.